2018
DOI: 10.1155/2018/1582173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adalimumab on the Expression Profile of Genes Associated with the Histaminergic System in the Skin Fibroblasts In Vitro

Abstract: Objective The aim of this study was to evaluate the influence of adalimumab on expression profile of genes associated with the histaminergic system in Normal Human Dermal Fibroblast (NHDF) cells stimulated with 8.00 μg/ml of adalimumab and the identification of miRNAs regulating these genes' expression. Methods NHDFs were cultured with or without the presence of adalimumab for 2, 8, and 24 hours. The expression profile of genes and miRNA were determined with the use of microarray technology. Results Among 2228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 55 publications
(46 reference statements)
1
26
0
5
Order By: Relevance
“…In the previous paper involving an in vitro model it was shown that changes at the transcriptome level after exposure of skin fibroblasts to adalimumab are possible to be detected after 2 hours of adding the drug to the culture. Moreover, the changes became less noticeable with prolonging the time of cell exposure to the drug [10].…”
Section: Discussionmentioning
confidence: 97%
“…In the previous paper involving an in vitro model it was shown that changes at the transcriptome level after exposure of skin fibroblasts to adalimumab are possible to be detected after 2 hours of adding the drug to the culture. Moreover, the changes became less noticeable with prolonging the time of cell exposure to the drug [10].…”
Section: Discussionmentioning
confidence: 97%
“…The identification of novel diagnostic and therapeutic molecular markers constitutes an enormous challenge in molecular biology. Analysis of the transcription changes of genes in molecularly targeted therapy is significant due to the fact that molecular changes precede phenotypic findings (Tables and ; Le Tourneau et al, ; Wcisło – Dziadecka et al, ). As such, an appropriately selected biological marker allows for the detection of a poor response to therapy at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…Na poziomie molekularnym łuszczyca objawia się zmianą stężeń cytokin, głównie interleukin (IL) -IL-12, (IL) -IL-12, IL-23, IL-17, IL-22 -tumour necrosis factor (TNF), interferon γ (IFN-γ), and transforming growth factor β1-3 (TGF-β1-3) [6,7].…”
Section: Molekularne Podłoże łUszczycy Jej Objawy Oraz Strategie Terunclassified